Review: Analisis Kandungan Klorin dan Formaldehid Pada Pembalut Wanita - Larasati, Fannisa Dini; Saputri, Safira Nurul Islam; Yollanda, Ade; Maelaningsih, Firdha Senja (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sanitary napkins are a medical device used during menstruation to absorb menstrual blood. Sanitary napkins are a product that uses chlorine as one of the ingredients, which can be used to clean sanitary napkins so they are always white (bleach). Apart from chlorine, formaldehyde can also be added to sanitary napkins to act as an anti-wetting agent and preservative. This research aims to discuss various studies related to the analysis of chlorine and formaldehyde content in sanitary napkins. This research analyzes the literature available in journals published in the last 10 years via Google Scholar. Chlorine analysis uses the iodometric titration, iodometric titration, argentometric titration, and UV-vis spectrophotometry methods. Meanwhile, formaldehyde analysis uses UV-vis spectrophotometry. The results of various studies show variations in the chlorine and formaldehyde content of the sanitary napkin samples tested.